Humanizing Artificial Intelligence Integration in English as a Foreign Language Pedagogy through Love and Empathy - Isaee, Hossein; Barjesteh, Hamed (Lia Center of Research and Education, 2025)
As artificial intelligence (AI) tools become part of daily teaching, questions arise about how teachers and learners can preserve emotional connection and ethical awareness in language classrooms. This study explored how EFL teachers and learners in Shiraz experience care, empathy, and human presence while using AI-supported tools. Guided by the framework of AI-informed Loving Pedagogy, it examined how both groups respond to the emotional and moral changes brought by digital mediation. Fifteen teachers and twenty learners participated in interviews and reflective journals over four weeks. Their narratives were analyzed thematically, leading to three main themes: Emotional Authenticity in Digital Interaction, Ethical Tensions and Affective Fatigue, and Reimagining Love through Technology. Results showed that both teachers and learners made conscious efforts to keep warmth and personal meaning alive in technology-rich settings. They often described a need to “sound human again” after AI-generated responses and felt torn between efficiency and emotional depth. Some also found new ways to express care through creative and ethical uses of AI. The findings suggest that love and empathy remain vital in digital pedagogy and can guide more ethical and sustainable AI use in language education. Teacher education should include emotional reflection and critical AI literacy to help educators design learning experiences that remain truly human-centered.